Interventions for head and neck cancer survivors: Systematic review. Issue 11 (18th July 2022) - Margalit, Danielle N.; Salz, Talya; Venchiarutti, Rebecca; Milley, Kristi; McNamara, Mairead; Chima, Sophie; Wong, Jamieson; Druce, Paige; Nekhlyudov, Larissa
Abstract: Background: Interventions for head/neck cancer (HNC) survivors may not address their cancer‐related and general health needs. Methods: Preferred Reporting Items for Systematic Reviews and Meta‐Analysis (PRISMA) guided this systematic review of studies from 2000 to 2021 of interventions targeting cancer survivors treated with curative‐intent, using MEDLINE, Embase, Emcare, and PsycINFO. Interventions were categorized into domains of the Quality of Cancer Survivorship Care Framework to characterize the scope and quality of interventions. Results: We identified 28 studies for inclusion: 13 randomized and 15 non‐randomized. Most targeted surveillance/management of physical effects ( n  = 24) including 13 that also targeted psychosocial effects. Four studies addressed prevention/surveillance for recurrence/new cancers, one addressed health promotion/disease prevention, and one addressed chronic medical conditions. Most studies ( n  = 27) had medium‐high risk of bias. Conclusions: There are few high‐quality studies addressing HNC survivorship. Future rigorously designed studies should address broader areas of care, including chronic disease management and health promotion/disease prevention.